(untitled) (Journal of EAHIL, 2017)
Candidate for Belgium - Inge Discart Candidate for Denmark - Jette Frost Jepsen Candidate for Finland - Elise Johansson Candidate for Finland - Tiina Heino Candidate for Italy - Valeria Scotti Candidate for Norway - Jannicke Rusnes Lie Candidate for Romania - Octavia-Luciana Madge Candidate for Slovenia - Vesna Cafuta Candidates for Spain - Rebeca Isabel Gómez, Alicia F. Gómez, Virgili Páez, Veronica Juan Quillis Candidates for Sweden - Sara Janzen, Marie Folkesson Jonsson, Yvonne Hultman Özek, Helen Sjöblom, Margareta Sundin, Linda Thorn Candidates for UK - Deirdre Beecher, Anne Donnelly, Isla Kuhn, Helen Buckley Woods Â